Word associations with "organic": what do consumers think of?. Issue 12 (5th December 2016) - Hilverda, Femke; Jurgens, Manon; Kuttschreuter, Margot
Abstract : Purpose: The purpose of this paper is to examine the word associations that consumers have with organic food, organic meat or organic vegetables, and how these associations differ between food type and consumer groups. Construal-level theory was used as a theoretical framework to interpret the associations. In addition, consumer groups were compared on psychological distance, values, age, and gender. Design/methodology/approach: Two studies were performed. In Study 1, a sample of 154 participants filled out the words that came to their mind when thinking of organic food, organic meat or organic vegetables, and psychological distance and values were measured. In Study 2 these words were rated on centrality by an independent sample ( n =52). Findings: Consumers think of animal welfare, price, health, pesticides, and naturalness the most when thinking of organic. The environment, health, honesty, pesticides, sustainability, quality, natural, additives, origin, certification, and taste were central across organic food, organic meat, and organic vegetables. Thinking of organic meat showed consumers' concern for animal welfare, while thinking of organic vegetables showed concern for human health. Consumer groups differed regarding psychological distance, values, gender, and age. Consumers who frequently bought organic food were more positive about organic food products compared to consumers who occasionally or hardly ever bought organic food products. Originality/value: This research extends the scope of current consumer research about organic food and provides new insight in the word associations consumers have with organic food products.